ASSESSMENT OF THE DEVELOPMENT OF UKRAINIAN ECONOMY BY THE COMPETITIVENESS RATING - Pogorielova, Anna; Zhurba, Yaroslav (Social Economics, 2018)
The era of globalization has caused an intensification of competition in the world market and international competitiveness has become one of the most complex phenomena of modern economic life, as a result of which it is necessary to monitor the level of global competitiveness so that Ukrainian institutions can ensure a stable growth rate. Solving the problem of low competitiveness will help the country to react in time to economic, technical and informational social changes occurring in the world and take the necessary measures to adapt to these changes. To strengthen competitive advantages among other countries in the world, it is necessary to interfere with innovative factors in the country's economy and promote sustainable development, which requires favorable conditions for business development.Given that the problem of competitiveness is key and practically meaningful both for countries that are already leaders in the competitiveness rating, and for countries that are still equal to world leaders. For our country, the issue of competitiveness is extremely acute, because now it is very important to increase the indicators of the Ukrainian economy in the context of its integration into the world economic space. Thus, the article analyzes the level of development of the Ukrainian economy in world ratings. Changes in the economy are traced by the dynamics of the Global Competitiveness Index between 2010 and 2017. It is determined that the quality of education and qualifications significantly influence the economic and social development of the country in the long term. The influence of a number of destabilizing factors that hinder economic development in Ukraine is analyzed. Factors for increasing the index in the rating for the period 2017-2018 have been singled out, and a forecast has been made on Ukraine's achievement of the results that will ensure the country's ranking among the top 40 places.